2020
DOI: 10.1038/s41598-020-58802-0
|View full text |Cite
|
Sign up to set email alerts
|

Culture modulates face scanning during dyadic social interactions

Abstract: Recent studies have revealed significant cultural modulations on face scanning strategies, thereby challenging the notion of universality in face perception. Current findings are based on screen-based paradigms, which offer high degrees of experimental control, but lack critical characteristics common to social interactions (e.g., social presence, dynamic visual saliency), and complementary approaches are required. The current study used head-mounted eye tracking techniques to investigate the visual strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 59 publications
4
36
0
Order By: Relevance
“…In line with the notion of gaze avoidance, East Asian dyads were expected to spend less time overall engaging in mutual gaze compared to Western Caucasian dyads, and were also predicted to show shorter individual instances of mutual gaze. With respect to face looking, we further expected increased face looking during listening compared to speaking periods in both cultural groups, as also reported in earlier face-to-face interaction studies (Freeth et al, 2013;Haensel et al, 2020). More face looking during the introductory period compared to the storytelling game was also expected in both cultural groups based on a previous cross-cultural social interaction study using the same experimental tasks (Haensel et al, 2020).…”
Section: The Current Studysupporting
confidence: 83%
See 3 more Smart Citations
“…In line with the notion of gaze avoidance, East Asian dyads were expected to spend less time overall engaging in mutual gaze compared to Western Caucasian dyads, and were also predicted to show shorter individual instances of mutual gaze. With respect to face looking, we further expected increased face looking during listening compared to speaking periods in both cultural groups, as also reported in earlier face-to-face interaction studies (Freeth et al, 2013;Haensel et al, 2020). More face looking during the introductory period compared to the storytelling game was also expected in both cultural groups based on a previous cross-cultural social interaction study using the same experimental tasks (Haensel et al, 2020).…”
Section: The Current Studysupporting
confidence: 83%
“…Looking at a face may reflect a way to better decode speech (Vatikiotis-Bateson et al, 1998), to signal attention to the speaker (Gobel et al, 2015;Risko et al, 2016), or an attempt to reduce cognitive load when speaking (Doherty-Sneddon & Phelps, 2005). In addition, both cultural groups also engaged in more face orienting during an introductory task relative to a storytelling game (Haensel et al, 2020), which had been suggested to result from social signalling during early introductory encounters, and the more demanding nature of the storytelling game that could have induced gaze aversion. Japanese participants also scanned the eye region more than British/Irish individuals; however, since only the eye movements of the participantand not the research assistantwere recorded, the study cannot inform about any cultural differences in two-way gaze dynamics including gaze avoidance.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…It is therefore not surprising that the majority of the interaction studies using wearable eye trackers included in this review did not distinguish between facial features and instead chose to make cruder distinctions, such as whether gaze was directed on the face (or object) or somewhere else (Broz et al, 2012;Damm et al, 2013;Franchak et al, 2011;Freeth et al, 2013;Fu, Nelson, Borge, Buss, & Pérez-Edgar, 2019;Gullberg & Holmqvist, 1999, 2006Hanna & Brennan, 2007;Ho et al, 2015;Macdonald & Tatler, 2013Nadig, Lee, Singh, Bosshart, & Ozonoff, 2010;Yamamoto, Sato, & Itakura, 2019;Yu & Smith, 2013Yu, Suanda, & Smith, 2019). Five of the reviewed studies with wearable eye trackers distinguished between gaze directed at different regions of the face: Cañigueral, Hamilton, and Ward (2018) and Cañigueral, Ward, and Hamilton (2020) divided the face into an eye region and a mouth region and Haensel et al (2020) divided the face into an upper and lower region, while Rogers, Speelman, Guidetti, and Longmuir (2018) and Freeth and Bugembe (2019) further differentiated between the finer details of the face (i.e., eyes, nose, mouth, etc. ).…”
Section: Data Qualitymentioning
confidence: 99%